2020
DOI: 10.1093/dote/doaa009
|View full text |Cite
|
Sign up to set email alerts
|

Barrett’s Registry Collaboration of academic centers in Ireland reveals high progression rate of low-grade dysplasia and low risk from nondysplastic Barrett’s esophagus: report of the RIBBON network

Abstract: Summary Barrett’s esophagus (BE) is the main pathological precursor of esophageal adenocarcinoma (EAC). Progression to high-grade dysplasia (HGD) or EAC from nondysplastic BE (NDBE), low-grade dysplasia (LGD) and indefinite for dysplasia (IND) varies widely between population-based studies and specialized centers for many reasons, principally the rigor of the biopsy protocol and the accuracy of pathologic definition. In the Republic of Ireland, a multicenter prospective registry and bioresource … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
0
8
0
4
Order By: Relevance
“…A systematic review and meta-analysis of 8 studies found that while the summary overall weighted annual incidence for progression to HGD/EAC was 4.6/100 patient-years (95% CI 2.0 -7.2), the rate was higher,at 8.8/100 patients, in the first year after diagnosis (181). Others have found a similar increase in risk in the first year after diagnosis, thereby emphasizing the importance of a careful repeat examination (182). Finally, there is considerable evidence that a diagnosis of confirmed LGD that persists on a second examination increases the risk for progression still further (34,183).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…A systematic review and meta-analysis of 8 studies found that while the summary overall weighted annual incidence for progression to HGD/EAC was 4.6/100 patient-years (95% CI 2.0 -7.2), the rate was higher,at 8.8/100 patients, in the first year after diagnosis (181). Others have found a similar increase in risk in the first year after diagnosis, thereby emphasizing the importance of a careful repeat examination (182). Finally, there is considerable evidence that a diagnosis of confirmed LGD that persists on a second examination increases the risk for progression still further (34,183).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Approximately 15–40% of all patients with BE are diagnosed with LGD at some point during their lifetime. LGD has been suggested to be a risk factor for progression to HGD/EAC 3,4 . Therefore, a clear management strategy for LGD is important.…”
Section: Introductionmentioning
confidence: 99%
“…LGD has been suggested to be a risk factor for progression to HGD/EAC. 3 , 4 Therefore, a clear management strategy for LGD is important. The management of LGD in BE is controversial due to various factors including variability in the natural history of LGD among different populations and interobserver variability among pathologist in its diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…examination as outlined below. 8 Finally, there is considerable evidence that a diagnosis of confirmed lowgrade dysplasia that persists on a second examination increases the risk for progression still further. 9 The issue of prevalent higher-level lesions is addressed in this issue of Gastrointestinal Endoscopy in the study by Tsoi et al, 10 who examined what happens to patients with diagnoses of Barrett's esophagus and low-grade dysplasia in the community setting when they were referred to any of 6 designated Barrett's expert tertiary care centers in Australia.…”
mentioning
confidence: 99%